2023
DOI: 10.1038/s41562-023-01577-x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic diversity fosters the social integration of refugee students

Abstract: Forced migration has become a global megatrend, and many refugees are school aged. As social integration is key to their wellbeing and success, it is pivotal to determine factors that promote the social integration of refugee youth within schools. Here, using a large, nationally representative social network dataset from Germany, we examine the relationships of refugee adolescents with their peers (304 classrooms, 6,390 adolescents and 487 refugees). We find that refugee adolescents have fewer friends and are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The establishment of trauma-sensitive concepts in schools underlines the importance of teachers as social caregivers ( Popham et al, 2023 ), and it emphasizes their importance in supporting social integration and, thus, the psychosocial development of students ( Boda et al, 2023 ). Social integration supports refugee students’ well-being, psychosocial development, and academic success ( Stadtfeld et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The establishment of trauma-sensitive concepts in schools underlines the importance of teachers as social caregivers ( Popham et al, 2023 ), and it emphasizes their importance in supporting social integration and, thus, the psychosocial development of students ( Boda et al, 2023 ). Social integration supports refugee students’ well-being, psychosocial development, and academic success ( Stadtfeld et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This not only makes it more difficult to resort to social support as an adaptive coping strategy through peers and advice from teachers, but it also impairs participation in lessons, which can have a negative effect on academic success. Trauma-affected children and adolescents are, therefore, more likely to be rejected by their peers ( Schwartz and Proctor, 2000 ; Boda et al, 2023 ) and show frequent school performance-related problems such as lower grade point averages and lower graduation rates ( Delaney-Black et al, 2002 ; Terrasi and De Galarce, 2017 ). On a psychological level, this can impair self-perception and negatively affect the school-related motivation of the children, which can lead to persistent learning deficits in the long term ( Lehman et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among refugee adolescents within the school context, peer relations operate as stronger determinants of perceived school belonging than relations with teachers or family members (Rizkallah, 2020). A nationally representative sample of German ninth graders found that refugee students are more often rejected by their peers as deskmates than their non‐refugee classmates and even more so in more homogenous (less ethnically diverse) classrooms (Boda et al, 2023). Further, perceived discrimination by peers in school is a significant source of distress and isolation, while social acceptance is associated with a sense of belonging in resettlement and leads to better academic and psychological outcomes (Kim et al, 2015; Samara et al, 2020).…”
Section: Understanding Unique Experiences Of Refugees With Universal ...mentioning
confidence: 99%